Steam Navigation and Its Relation to the Commerce of Canada and the United States - Croil, James, 1821-1916 (Salt Lake City, UT : Project Gutenberg, 2019)
"Steam Navigation and Its Relation to the Commerce of Canada and the United States" by James Croil is a historical account written in the late 19th century. The book explores the origins, development, and impact of steam navigation on commerce between Canada and the United States, highlighting significant steam vessels and their contributions to trade and transportation. The opening of the work presents a detailed preface that outlines the motivations behind the book and acknowledges other notable writings on the subject. Croil expresses a deep passion for steam navigation, citing its revolutionary role in connecting distant lands and facilitating trade. He mentions the plethora of sources he has drawn upon to compile his narrative, indicating a meticulous approach to documenting the history of steam vessels, particularly those related to Canadian waterways. This sets the stage for a comprehensive exploration of the evolution of steam navigation that the forthcoming chapters promise to elaborate on in more detail. (This is an automatically generated summary.)
Release date is 2019-02-10
E-text prepared by Paul Marshall, Donald Cummings, Adrian Mastronardi, the Philatelic Digital Library Project (https://www.librarything.com/groups/tpdlp) and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Steam-navigation -- History; Shipping -- Canada -- History; Shipping -- United States -- History